Normative Legitimacy of Village Regulations Beyond the Statutory Hierarchy: Reconstructing Their Legal Status in Indonesia - Wahyu Prianto; Erna Kurniawati (Universitas Islam Negeri Raden Intan Lampung, 2026)
This article examines the legal standing and legitimacy of Village Regulations (Peraturan Desa/Perdes) in the Indonesian legislative system after the enactment of Law No. 12 of 2011. Since Perdes is no longer expressly included in the hierarchy of laws and regulations under Article 7(1), questions arise regarding its normative validity and position within the national legal order. This study aims to analyze the normative legitimacy of Village Regulations, identify their legal status within Indonesia’s legislative system, and explain the implications of that status for village autonomy and the potential for vertical disharmony in legal control mechanisms. This research applies a statutory and conceptual approach, employing descriptive-qualitative analysis and Hans Kelsen’s Stufenbau theory to assess the validity and interrelation of Perdes within the structure of legal norms. The findings show that although Village Regulations are no longer part of the main hierarchy, they remain legally recognized and binding. However, their validity largely depends on authority derived from higher-level regulations, making them derivative in nature. This condition affects the exercise of village autonomy, which depends not only on delegated authority but also on institutional readiness and village regulatory capacity. In addition, vertical disharmony may occur between administrative supervision by regents/mayors and judicial review by the Supreme Court. The study recommends clearer legal construction of Perdes, a firmer distinction between preventive supervision and repressive judicial review, and stronger village legislative capacity.